건성안에서 눈물점마개의 치료와 탈락률에 대한 임상 고찰 - 권정도; Jeong Do Kwon; 박도훈; Do Hoon Park; 박동; Dong Park; 이창환; Chang Hwan Lee (Daihan angwa haghoi jabji, 2006)
목적 : 실리콘 눈물점마개의 장기 경과에 따른 탈락률과 시술 전후와 탈락 유무에 따른 치료효과에 관해 알아보았다. 대상과 방법 : 2003년 5월부터 2004년 6월까지 수성눈물결핍형 건성안으로 진단되어 눈물점마개 삽입술을 시행 받은 60명 120안에 대해 평균 382.3±164.3일간 경과관찰하여 탈락률과 탈락까지의 기간, 시술 전후와 탈락 유무에 따른 객관적 및 주관적 건성안 지표의 차이에 대해 검토하였다. 결과 : 눈물점마개의 탈락은 31안(25.8%)에서 관찰되었고, 100일 미만이 13안(41.9%)으로 가장 많았다. 시술 전후로 측정하였던 객관적 지표인 Schirmer test와 BUT는 통계학적으로 유의하게 증가하였다. 주관적 지표인 건성안의 임상증상은 시술후에 통계학적으로 유의하게 호전되었으며, 인공눈물 점안 횟수는 70.8%에서 중단하거나 감소했으나 각 경우에서 탈락 유무에 따른 차이는 없었다. 결론 : 건성안의 치료에서 실리콘 눈물점마개는 효과적인 치료법이나 탈락률이 비교적 높다. 그러나, 눈물점마개가 탈락한 경우에도 눈물소관내 상피의 과도증식에 의한 협착으로 증상의 호전이 가능하다. 시술전 탈락률과 경과에 대한 정확한 설명은 치료 순응도 증가와 의사-환자 관계 형성에 도움이 될 것이다. <한안지 47(8):1204-1211, 2006> Purpose: To investigte the extrusion rate of punctal plugs and to evaluate their long-term effectiveness related to punctal occlusion. Methods: The subjects were 120 eyes of 60 patients with tear-deficient dry eye who underwent punctal occlusion using a silicone punctal plug from May 2003 to Jun 2004. They were followed up for 382.3±164.3 days. We studied the extrusion rate and the period of extrusion for each plug and examined the differences between the objective and subjective indicators of dry eye syndrome before and after plug insertion and between extruded and non-extruded punctal plugs. Results: In this study, 25.8% of all plugs were extruded during the follow-up period. The majority of plugs (41.9%) were extruded within 100 days after plug insertion. As objective indicators, results of Schirmer test and BUT were significantly increased after plug insertion. As subjective indicators, the patients` clinical symptoms significantly improved. Patient use of artificial tear drops significantly decreased and was discontinued by 70.8% after plug insertion. There were however no significant differences between the extrusion group and the non-extrusion group in each case. Conclusions: Punctal plug occlusion therapy for tear-deficient dry eye is effective, but the extrusion rate is relatively high. Regardless of punctal plug extrusion, patients experienced a symptomatic improvement. Serious consideration of this fact may greatly aid in making therapeutic adaptations and maintaining a good relationship. J Korean Ophthalmol Soc 47(8):1204-1211, 2006